Character Education Values in the Children's Animated Movie Channel Youtube Nussa Official / Nilai-Nilai Pendidikan Karakter dalam Film Animasi Anak Channel Youtube Nussa Official - Munir, Misbahul; Nur Rokhmah, Ummi (Al-Mudarris: Journal Of Education, 2020)
The aim of this research is to get an overview of the values of character education in the animated film Nussa Rara Official youtube channel production. In this research using descriptive analysis method, the data taken in this study is a dialogue on the episode who are we ?, eat not just eat, be independent !!!, which contains the value of character education. The value of character education that appear among them, trying to know the solar system, attitudes and behavior that adhere to the eating procedures that have been taught by the Prophet, the behavior shows a sincere effort to get the best results, actions that show a sense of happiness in working together and mutual help, encouraging and acknowledging the success of others. The relevance of the value of character education on Nussa's official youtube channel among them curiosity, religious, hard work, friendly or communicative, appreciate chievement.